SAT0726-HPR Functional impairment in patients with ra in an eight year perspective. (15th June 2017) - Bremander, A; Forslind, K; Eberhardt, K; Andersson, M
Abstract : Background: In people with Rheumatoid arthritis (RA) impaired physical functioning is an acute as well as long term effect of the disease. Observational performance tests reflecting range of motion in upper as well as in lower extremities should be easy to perform in the clinic as well as in research as a complement to self-reported measures of physical functioning. The Signal Of Functional Impairment (SOFI) 1 is a performance test which so far has been applied only in Sweden but commonly used in the clinic and in long term follow-up clinical studies. Objectives: The aim was to study performance-based function assessed with SOFI over 8 years and, secondly, to study which items included in SOFI that were associated with change in functioning over time. Methods: An inception cohort of 1 052 patients with early RA, from the BARFOT-study, recruited 1992–2006 was investigated, mean (SD) age was 54 years (14), 70% were women. The patients were followed by a structured protocol at baseline, 3 and 6 months and at 1, 2, 5, and 8 years. SOFI consists of 3 parts measuring hand, arm (upper), and leg (lower) function (1). Hand function is tested by 4 movements; cylinder grip (H1), pen grip (H2), pincer grip (H3) and opposition of the thumb (H4). Arm function is assessed by 3 movements; hand behind the head and the ability to touch the cervical spine processes with fingers (A1), elbow supination (A2) and elbow extension (A3). Leg function is tested by 4 movements; the ability to touch the opposite knee with the heel while sitting (L1), knee extension in supine position (L2), dorsiflexion of the foot standing on a balance board (L3), and the ability to stand on tip toes without shoes (L4). An assessor scores the patient's ability to perform the different tests on an ordinal scale (0=normal, 1= partly impaired and 2= unable to perform). The range of SOFI scores is 0–44 (best to worst). Results: At baseline the mean (SD) SOFI was 7.2 (5.8), and at 1 year follow-up the improvement was 2.75 (5.65), p<0.001. From 1 year to 8 year follow-up the deterioration was 1.5 (4.6), p<0.001. When studying hand, upper and lower function separately, the pen grip and the ability to stand on tip toes improves most during the first year. From 1 to 8 year the pincer grip and the ability to stand on tip toes are the items that deteriorate most (Figure). Assessment of the pen grip, the pincer grip and the ability to stand on tip toes explain 58% to 70% of the SOFI score over time, with the highest rate at 5 (65%) and 8 years follow-up (70%). Conclusions: Functioning as assessed by SOFI improved during the first year in patients with early RA and then deteriorated slowly. Over a longer period, pincer grip and the ability to stand on tip toes seemed to be the two most important items to measure when assessing functional impairment over time. References: Kerstin B. Eberhardt, B. Svensson and U. Moritz. Functional assessment of early rheumatoid arthritis British Journal of Rheumatology 1988;27:364–371. Disclosure of Interest: None declared